2018
DOI: 10.1021/acs.langmuir.8b01850
|View full text |Cite
|
Sign up to set email alerts
|

Control of Membrane Binding and Diffusion of Cholesteryl-Modified DNA Origami Nanostructures by DNA Spacers

Abstract: DNA origami nanotechnology is being increasingly used to mimic membrane-associated biophysical phenomena. Although a variety of DNA origami nanostructures has already been produced to target lipid membranes, the requirements for membrane binding have so far not been systematically assessed. Here, we used a set of elongated DNA origami structures with varying placement and number of cholesteryl-based membrane anchors to compare different strategies for their incorporation. Single and multiple cholesteryl anchor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 76 publications
1
41
0
Order By: Relevance
“…GUVs, comprising DOPC with 0.1 mol % fluorescently labeled 1,2-dioleoyl- sn -glycero-3-phosphoethanolamine (Atto488-DOPE), were prepared by electroformation in 52 mM sucrose. 16,17 Triskelion dimers with Alexa647 labels (Supporting Figure S1) were assembled in equiosmolar TE-MgCl 2 buffer, incubated for at least 10 min with the GUV suspension diluted 20-fold in the same TE-MgCl 2 buffer (Supporting Figure S14), and observed using confocal microscopy. Dimers were observed to bind to membranes homogeneously and diffuse freely (Figure 2A,B and Supporting Movie M1).…”
Section: Results and Discussionmentioning
confidence: 99%
“…GUVs, comprising DOPC with 0.1 mol % fluorescently labeled 1,2-dioleoyl- sn -glycero-3-phosphoethanolamine (Atto488-DOPE), were prepared by electroformation in 52 mM sucrose. 16,17 Triskelion dimers with Alexa647 labels (Supporting Figure S1) were assembled in equiosmolar TE-MgCl 2 buffer, incubated for at least 10 min with the GUV suspension diluted 20-fold in the same TE-MgCl 2 buffer (Supporting Figure S14), and observed using confocal microscopy. Dimers were observed to bind to membranes homogeneously and diffuse freely (Figure 2A,B and Supporting Movie M1).…”
Section: Results and Discussionmentioning
confidence: 99%
“…41 The augmented affinity to cell membranes with cholesteryl anchors was further reported with modified hyaluronan, 46 or DNA. 47 The differences in CTA groups on cellular uptake might be explained by the involvement of cells in lipid uptake. Cholesterol can interact with other proteins via both covalent 48 and noncovalent mechanisms, 49,50 thereby regulating protein stability, localization, 51 and activity.…”
Section: Discussionmentioning
confidence: 99%
“…In this methodology, DNA’s specific base-pairing and self-assembly properties are exploited to use it as a structural material to generate objects of pre-designed shapes [90]. Taking advantage of this programmability, DNA origami has successfully been employed to achieve membrane binding [91, 92] and transformation [93, 94]. For example, we have shown that variably curved DNA origami objects mimicking banana-shaped BAR domains, targeted to membranes via cholesterol anchors, can recognize and deform GUVs [94].…”
Section: Synthetic Cell Division Based On Non-natural Biomolecular Comentioning
confidence: 99%